Acceleration of Mega Merger of SOE Sharia Banks in Indonesia through Revitalization of Sharia Economic Law in Islamic Boarding Schools - Ferry Jie; Harisah Harisah; Zubaidi Sulaiman (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2020)
Generally, we can see that law is all rules of behavior in norms regulating orders among societies. Likewise, sharia economic law regulates the community's policies in economic activities, and the application of this rule in Indonesia can be studied through Islamic boarding schools as a place for Islamic scientific education. The condition of this Indonesian pesantren is no longer only studying classical sciences. Accordingly, the program has become one of the instruments for accelerating the mega-merger of Islamic banks. This research used qualitative methods with data collection through interviews and direct observations. This study found that Islamic boarding schools in Indonesia have provided Islamic economic, scientific facilities, and microfinance institutions to support learning Islamic economic law and introduce knowledge.